The Impact of Viral Marketing, Online Customer Review, and Online Customer Rating on Online Shopping Decisions in The Tokopedia Marketplace of Universitas Diponegoro Students - Anissa Rizqi Adha; Widiartanto Widiartanto; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2023)
Tokopedia in the past year has not become a trend and could not achieve enough of their popularity in the community, negative reviews, and low ratings for certain of products also makes people reluctant to choose to buy online through Tokopedia. So, by looking at the existing problems, this research was conducted with the aim of knowing the impact of Viral Marketing, Online Customer Review, and Online Customer Rating on Online Shopping Decisions in the Tokopedia Marketplace of Universitas Diponegoro Students. The number of samples is 118 respondents with a non-probability sampling technique, namely purposive sampling. This type of research is explanatory research which is processed using SPSS V25 software. Data processing was carried out using validity and reliability tests, correlation coefficients, determination coefficients, simple linear regression, multiple linear regression, t-test, and F-test. The conclusion from this study is that the Viral Marketing variable has no significant effect on the Online Shopping Decisions variable, the Online Customer Review variable has a significant effect on the Online Shopping Decisions variable, and the Online Customer Rating variable has a significant effect on the Online Shopping Decisions variable.